Monetary policy with incomplete exchange rate pass-through - Malin Adolfson (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
The central bank's optimal reaction to foreign and domestic shocks is analyzed in an inflation targeting model allowing for incomplete exchange rate pass-through. Limited pass-through is incorporated through nominal rigidities in an aggregate supply-aggregate demand model derived from some microfoundations. Three main results are obtained. First, the results suggest that the interest rate response to foreign shocks is smaller when pass-through is low. Second, the inflation-output variability trade-off becomes more favourable as pass-through decreases. Third, lower pass-through, that is larger nominal rigidity, leads to higher exchange rate volatility. With exogenous nominal price stickiness, part of the required relative price adjustment is provided through larger movements in the endogenously determined exchange rate.
Keywords: E52; E58; F41; 330; Exchange rate pass-through; exchange rate volatility; inflation targeting; monetary policy; small open economy; Geldpolitik; Exchange Rate Pass-Through; Schock; Kleines-offenes-Land; Theorie